2018
DOI: 10.1038/s41396-018-0171-4
|View full text |Cite
|
Sign up to set email alerts
|

Signal beyond nutrient, fructose, exuded by an arbuscular mycorrhizal fungus triggers phytate mineralization by a phosphate solubilizing bacterium

Abstract: Cooperation is a prevalent phenomenon in nature and how it originates and maintains is a fundamental question in ecology. Many efforts have been made to understand cooperation between individuals in the same species, while the mechanisms enabling cooperation between different species are less understood. Here, we investigated under strict in vitro culture conditions if the exchange of carbon and phosphorus is pivotal to the cooperation between the arbuscular mycorrhizal fungus (AMF) Rhizophagus irregularis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 197 publications
(152 citation statements)
references
References 46 publications
8
128
0
Order By: Relevance
“…The distinction between saprotrophic and hypersymbiotic microbes in this regards is the origin of C the microbes live on-either from the SOM or from the AMF hyphae, respectively. A nice example of a tight cooperation between the AMF hyphae and a soil bacterium Rahnella aquatilis with regards to organic P (phytate) mineralization has recently been described by Zhang et al [136]. Although mineralization of organic N is at least equally important process as organic P mineralization, and microbial communities in AMF hyphosphere amended with organic N have been analyzed previously [16,43,96], there is as yet no specific information about the identity of primary organic N decomposers teaming directly with the AMF hyphae.…”
Section: Organic Nitrogen In Soil and Am Symbiosismentioning
confidence: 94%
“…The distinction between saprotrophic and hypersymbiotic microbes in this regards is the origin of C the microbes live on-either from the SOM or from the AMF hyphae, respectively. A nice example of a tight cooperation between the AMF hyphae and a soil bacterium Rahnella aquatilis with regards to organic P (phytate) mineralization has recently been described by Zhang et al [136]. Although mineralization of organic N is at least equally important process as organic P mineralization, and microbial communities in AMF hyphosphere amended with organic N have been analyzed previously [16,43,96], there is as yet no specific information about the identity of primary organic N decomposers teaming directly with the AMF hyphae.…”
Section: Organic Nitrogen In Soil and Am Symbiosismentioning
confidence: 94%
“…By contrast, whereas AM fungi can take up and transfer N from organic matter to their host plant (Hodge et al, 2001;Fellbaum et al, 2012;Thirkell et al, 2016), the weight of evidence is that AM fungi take up N or P primarily after mineralization by other soil microbes (Joner & Jakobsen, 1995;Leigh et al, 2009;Whiteside et al, 2012;Wang et al, 2017). Indeed, there is increasing evidence that AM hyphae can stimulate mineralization of organic matter by influencing the metabolism of soil bacteria (Zhang et al, 2018) and compete effectively with soil microbes for those nutrients (Bukovsk a et al, 2018).…”
Section: New Phytologistmentioning
confidence: 99%
“…In recent years, mycorrhizal genome sequencing studies have found that mycorrhizal fungi have lost many saprophytic genes in the longterm co-evolution process with plants [16]. Cooperating with functional microbiomes, such as phosphatase releasing bacteria [6,41] is considered an important strategy for AM fungi to compensate their lack of ability to utilize organic P. We find for the first time that different living AM fungi species that colonized single plant root recruit active microbiomes which are distinct from each other. The research not only provides direct evidence for understanding the biophysical process that AM fungal hyphae exudates drive the formation of soil bacteria diversity heterogeneity, but also reveals the potential division of labor may exist in plant-AM fungi-bacteria system that still remains to be understood fully.…”
Section: Outlook and Conclusionmentioning
confidence: 76%